Question
upstudy study bank question image url

5.3 Simplify the following to a single trigonometric function, without the calculator. \( \frac{\cos \left(90^{\circ}-\alpha\right) \sin \left(-\alpha-540^{\circ}\right)}{\tan 225^{\circ}+\sin \alpha \cdot \sin \left(180^{\circ}+\alpha\right)} \)

Ask by Vaughn Hart. in South Africa
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The expression simplifies to \( \tan^2 \alpha \).

Solution

We start with the given expression:   [cos(90° – α) · sin(–α – 540°)] ÷ [tan 225° + sin α · sin(180° + α)] Step 1. Simplify the numerator. • Use the co-function identity: cos(90° – α) = sin α. • Now, simplify sin(–α – 540°). Recognize that sine is periodic with a period of 360°:   sin(–α – 540°) = sin(–α – 540° + 720°) = sin(180° – α).   Recall the identity: sin(180° – α) = sin α. Thus, the numerator becomes:   sin α · sin α = sin²α. Step 2. Simplify the denominator. • Recall that tangent has a period of 180°:   tan 225° = tan(225° – 180°) = tan 45° = 1. • Simplify sin(180° + α) using the sine addition property:   sin(180° + α) = – sin α.   So, sin α · sin(180° + α) = sin α · (– sin α) = – sin²α. Thus, the denominator becomes:   1 + (– sin²α) = 1 – sin²α. Step 3. Combine the results. The expression is now:   (sin²α) ÷ (1 – sin²α). Recall the Pythagorean identity:   1 – sin²α = cos²α. Thus, the expression simplifies to:   sin²α ÷ cos²α = (sin α/cos α)² = tan²α. Final Answer: tan²α.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To simplify the given expression, let's break it down step-by-step. 1. **Evaluate the components:** - \(\cos(90^{\circ}-\alpha) = \sin(\alpha)\) (using the co-function identity) - \(\sin(-\alpha - 540^{\circ})\): First, simplify \(-540^{\circ}\) to \(-540 + 720 = 180^{\circ}\). So, \(\sin(-\alpha - 540^{\circ}) = \sin(-\alpha + 180^{\circ}) = -\sin(\alpha)\) (since \(\sin(180^{\circ} + x) = -\sin(x)\)). - \(\tan(225^{\circ}) = \tan(180 + 45^{\circ}) = \tan(45^{\circ}) = -1\). - \(\sin(180^{\circ} + \alpha) = -\sin(\alpha)\). 2. **Substituting back into the expression:** The expression now looks like this: \[ \frac{\sin(\alpha)(-\sin(\alpha))}{-1 + \sin(\alpha)(-\sin(\alpha))} \] This simplifies to: \[ \frac{-\sin^2(\alpha)}{-1 - \sin^2(\alpha)} \] 3. **Further simplify the denominator:** The denominator \(-1 - \sin^2(\alpha) = - (1 + \sin^2(\alpha))\). Thus, the expression simplifies to: \[ \frac{-\sin^2(\alpha)}{- (1 + \sin^2(\alpha))} = \frac{\sin^2(\alpha)}{1 + \sin^2(\alpha)} \] 4. **Final Result:** So, the final simplified expression is: \[ \frac{\sin^2(\alpha)}{1 + \sin^2(\alpha)} \]

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy